Examining the Reality of Foreign National Child Victims of Human Trafficking in the United States - Bridgette Carr (Washington University Journal of Law & Policy, 2011)
From its inception, the Trafficking Victims Protection Act (TVPA) has been touted as a tool to combat grave human rights violations that affect children. In fact, the TVPA's legislative history is rife with stories, statistics, and anecdotes involving children—often young girls. The TVPA has always recognized the failure of a one-size-fits-all approach for victims of trafficking, and that the needs of child victims can be quite different than the needs of adult victims. In light of this reality, a number of TVPA provisions make special exceptions or accommodations for children. On paper, these accommodations may seem satisfactory. Unfortunately, for trafficked children within the immigration system, like the ones described below, the reality can be quite different.
Keywords: Child sexual exploitation; Child welfare; Human smuggling; Immigrant children; Trafficking Victims Protection Reauthorization Act of 2003; Victims of Trafficking and Violence Prevention Act of 2000; International; United States